Price theory and its uses - Watson, Donald Stevenson (Boston : Houghton Mifflin, 1963)
The concepts and method of analysis provide a way of thinking helpful in many kinds of business problems, in the appraisal of economic policies of government, and in serious reflection on the meaning of private enterprise in the world today.
Includes bibliographical references and index.
osa 16/01/2019
Loans
Keywords: Prices